(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Quality checking is an important process that is used in a wide range of applications. From all the product and necessary equipment of the all systems, we see a major reliance on correctness of product. In this project we focus on quality checking of product. The understanding of the checking of component and their different factors that contributes to part quality. We acquired primary checking skills that provided us an opportunity to make this project. For each component, we created a detailed engineering working drawing that helped to shape and construct all the operations and procedures that must be undertaken and controlled to attain component checking without any obstruct the product. Through this project, we discovered many different factors involved in checking and the effects they exhibited on the quality of a part. The main relevant factors that we examined were set-up selection. The extent to which these factors can influence machining is presented.